Preparation method of latex beaded heat-insulating gloves
Through the molding and forming process and vulcanization treatment of latex beaded glue and latex impregnated glue, combined with the design of the glue-impregnated layer, the problems of inflexible operation and poor thermal insulation performance of existing heat insulation gloves are solved, and higher isolation is achieved Heat and grip.
Patent Information
- Application Number
- CN202111445867.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-11-30
AI Technical Summary
The existing thermal insulation gloves are not flexible enough, have weak grip, and have poor thermal insulation performance, making them difficult to be suitable for high-temperature environment operations.
Latex dot glue and latex impregnated glue are used to form latex dot beads through molding and molding. Combined with vulcanization treatment and the design of the glue-impregnation layer, it enhances the thermal insulation and grip of the gloves.
It improves the thermal insulation and grip of the gloves, enhances the durability and flexibility of the gloves, and is suitable for operations in high-temperature environments.
Smart Images

Figure BDA0003383161950000171 
Figure BDA0003383161950000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of beaded gloves production, and more specifically, to a method for preparing latex beaded heat-insulating gloves. Background Art
[0002] Gloves play a great role in protecting workers' hands during industrial production. Protective gloves include chemical protection, cut protection, electrical insulation, waterproof, cold protection, heat insulation, fire retardant and other functional gloves. Workers in different fields such as metallurgy, electronics, precision instruments, biopharmaceuticals, and food can work in high temperature environments by wearing heat insulation gloves.
[0003] Existing heat-insulating gloves are mainly sewn gloves made of cowhide, aramid, glass fiber, silicone dipping, etc. They are thick and wide in appearance, not flexible in operation, and have weak grip. Ordinary latex gloves have poor heat insulation performance and are not applicable. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing latex beaded heat-insulating gloves to solve one or more of the above-mentioned problems.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0007] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0008] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0009] S3, putting the glove core covered with beads in step S2 onto the hand model;
[0010] The oven temperature is raised and maintained at 55-60°C;
[0011] Place the glove core in an oven and bake for 15-20 minutes for preheating;
[0012] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0013] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0014] Pre-sulfurization treatment is carried out after 60-120S of glue spreading;
[0015] The temperature of pre-sulfur treatment is 75-90℃, and the pre-sulfur time is 30-40min;
[0016] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0017] The temperature for soaking and washing is 25-30℃, and the time for soaking and washing is 15-20min;
[0018] The temperature of high temperature vulcanization treatment is 95-110℃, and the treatment time is 40-80min;
[0019] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0020] Furthermore, the raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0021] 100 parts of natural latex, 1-3 parts of KOH, 0.8-1.6 parts of sulfur, 1.6-2.4 parts of zinc oxide, 0.6-1.2 parts of accelerator, 1-3 parts of antioxidant, 3-5 parts of thermal insulation filler, 1-3 parts of black pigment, 1-3 parts of thermal sensitizer, 4-8 parts of cellulose;
[0022] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0023] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0024] Continue to add the thermosensitive agent and stir;
[0025] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0026] Furthermore, in the method for preparing the latex bead glue, the foaming amount is controlled at 30±10%, and the viscosity is controlled at 6000±500 mPas.
[0027] Furthermore, the raw materials used for the latex impregnation mortar in step S1 are the following formula by weight:
[0028] 100 parts of natural latex, 1-3 parts of KOH, 0.8-1.6 parts of sulfur, 1.6-2.4 parts of zinc oxide, 0.6-1.2 parts of accelerator, 1-3 parts of antioxidant, 1-3 parts of black pigment, 2-4 parts of cellulose;
[0029] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0030] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0031] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0032] Furthermore, in the method for preparing the latex impregnation slurry, the foaming amount is controlled at 25±5%, and the viscosity is controlled at 1200±200 mPas.
[0033] Furthermore, the accelerator is diphenylthiourea, and the antioxidant is antioxidant 2246;
[0034] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0035] Furthermore, the compression molding process in step S2 includes the following steps:
[0036] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0037] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0038] Heat and maintain the temperature at 100-110°C, pressurize and maintain at 0.1-0.4MPa;
[0039] After 1-5 minutes, the beads are formed on the surface of the glove core.
[0040] Furthermore, the height of the beads formed on the surface of the glove core is 4-6 mm, and the spacing is 2-3 mm.
[0041] Furthermore, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4±1%;
[0042] The homogenization time is 80-100s.
[0043] In summary, the present invention has the following beneficial effects:
[0044] By increasing the height of the latex beads, improving the formula and enhancing the heat insulation of the tiger's mouth to increase the heat transfer barrier when grasping objects, the heat insulation of the gloves is greatly improved. By rationally designing the spacing of the latex beads and the pattern of the bead area, the gloves are easy to bend when grasping objects, making them more flexible and convenient. The dipped layer outside the latex beads and the beads are tightly bonded through vulcanization, and the durability is greatly improved. The special design of the heat insulation function of the latex layer has development advantages. DETAILED DESCRIPTION
[0045] Example 1
[0046] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0047] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0048] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0049] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 3 parts of thermal insulation filler, 2 parts of black pigment, 2 parts of thermal sensitizer, 6 parts of cellulose;
[0050] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0051] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0052] Continue to add the thermosensitive agent and stir;
[0053] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0054] In the preparation method of the latex bead glue, the foaming amount is controlled at 30%, and the viscosity is controlled at 5500mPas.
[0055] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0056] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 2 parts of black pigment, 3 parts of cellulose;
[0057] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0058] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0059] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0060] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 20% and the viscosity is controlled at 1200 mPas.
[0061] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0062] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0063] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0064] The compression molding process in step S2 includes the following steps:
[0065] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0066] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0067] Heating and maintaining the temperature at 105°C, pressurizing and maintaining at 0.3MPa;
[0068] After 1 minute, beads are formed on the surface of the glove core.
[0069] The height of the beads formed on the surface of the glove core is 4mm and the spacing is 2mm.
[0070] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0071] Wherein, the preheating treatment in step S3 includes the following steps:
[0072] The oven temperature was raised and maintained at 60°C;
[0073] The glove core was placed in an oven and baked for 15 min.
[0074] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0075] Wherein, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4%;
[0076] The homogenization time is 90s.
[0077] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0078] Pre-sulfur treatment is carried out after 60S of glue mixing;
[0079] The pre-sulfurization temperature is 80°C and the pre-sulfurization time is 40 minutes;
[0080] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0081] The temperature of the bath is 25℃ and the time of the bath is 20min.
[0082] The temperature of high temperature vulcanization treatment is 100°C and the treatment time is 80min;
[0083] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0084] Example 2
[0085] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0086] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0087] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0088] 100 parts of natural latex, 2 parts of KOH, 1.26 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 3 parts of thermal insulation filler, 2 parts of black pigment, 2 parts of thermal sensitizer, 6 parts of cellulose;
[0089] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0090] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0091] Continue to add the thermosensitive agent and stir;
[0092] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0093] In the preparation method of the latex bead glue, the foaming amount is controlled at 30%, and the viscosity is controlled at 5500mPas.
[0094] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0095] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 2 parts of black pigment, 3 parts of cellulose;
[0096] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0097] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0098] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0099] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 20% and the viscosity is controlled at 1200 mPas.
[0100] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0101] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0102] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0103] The compression molding process in step S2 includes the following steps:
[0104] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0105] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0106] Heating and maintaining the temperature at 105°C, pressurizing and maintaining at 0.3MPa;
[0107] After 1 minute, beads are formed on the surface of the glove core.
[0108] The height of the beads formed on the surface of the glove core is 6mm and the spacing is 2mm.
[0109] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0110] Wherein, the preheating treatment in step S3 includes the following steps:
[0111] The oven temperature was raised and maintained at 60°C;
[0112] The glove core was placed in an oven and baked for 15 min.
[0113] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0114] Wherein, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4%;
[0115] The homogenization time is 90s.
[0116] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0117] Pre-sulfur treatment is carried out after 60S of glue mixing;
[0118] The pre-sulfurization temperature is 80°C and the pre-sulfurization time is 40 minutes;
[0119] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0120] The temperature of the bath is 25℃ and the time of the bath is 20min.
[0121] The temperature of high temperature vulcanization treatment is 100°C and the treatment time is 80min;
[0122] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0123] Example 3
[0124] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0125] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0126] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0127] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 5 parts of thermal insulation filler, 2 parts of black pigment, 2 parts of thermal sensitizer, 6 parts of cellulose;
[0128] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0129] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0130] Continue to add the thermosensitive agent and stir;
[0131] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0132] In the preparation method of the latex bead glue, the foaming amount is controlled at 30%, and the viscosity is controlled at 5500mPas.
[0133] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0134] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 2 parts of black pigment, 3 parts of cellulose;
[0135] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0136] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0137] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0138] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 20% and the viscosity is controlled at 1200 mPas.
[0139] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0140] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0141] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0142] The compression molding process in step S2 includes the following steps:
[0143] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0144] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0145] Heating and maintaining the temperature at 105°C, pressurizing and maintaining at 0.3MPa;
[0146] After 1 minute, beads are formed on the surface of the glove core.
[0147] The height of the beads formed on the surface of the glove core is 4mm and the spacing is 2mm.
[0148] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0149] Wherein, the preheating treatment in step S3 includes the following steps:
[0150] The oven temperature was raised and maintained at 60°C;
[0151] The glove core was placed in an oven and baked for 15 min.
[0152] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0153] Wherein, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4%;
[0154] The homogenization time is 90s.
[0155] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0156] Pre-sulfur treatment is carried out after 60S of glue mixing;
[0157] The pre-sulfurization temperature is 80°C and the pre-sulfurization time is 40 minutes;
[0158] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0159] The temperature of the bath is 25℃ and the time of the bath is 20min.
[0160] The temperature of high temperature vulcanization treatment is 100°C and the treatment time is 80min;
[0161] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0162] Example 4
[0163] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0164] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0165] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0166] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 3 parts of thermal insulation filler, 2 parts of black pigment, 2 parts of thermal sensitizer, 6 parts of cellulose;
[0167] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0168] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0169] Continue to add the thermosensitive agent and stir;
[0170] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0171] In the preparation method of the latex bead glue, the foaming amount is controlled at 40%, and the viscosity is controlled at 5500mPas.
[0172] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0173] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 2 parts of black pigment, 3 parts of cellulose;
[0174] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0175] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0176] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0177] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 20% and the viscosity is controlled at 1200 mPas.
[0178] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0179] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0180] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0181] The compression molding process in step S2 includes the following steps:
[0182] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0183] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0184] Heating and maintaining the temperature at 105°C, pressurizing and maintaining at 0.3MPa;
[0185] After 1 minute, beads are formed on the surface of the glove core.
[0186] The height of the beads formed on the surface of the glove core is 4mm and the spacing is 2mm.
[0187] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0188] Wherein, the preheating treatment in step S3 includes the following steps:
[0189] The oven temperature was raised and maintained at 60°C;
[0190] The glove core was placed in an oven and baked for 15 min.
[0191] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0192] Wherein, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4%;
[0193] The homogenization time is 90s.
[0194] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0195] Pre-sulfur treatment is carried out after 60S of glue mixing;
[0196] The pre-sulfurization temperature is 80°C and the pre-sulfurization time is 40 minutes;
[0197] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0198] The temperature of the bath is 25℃ and the time of the bath is 20min.
[0199] The temperature of high temperature vulcanization treatment is 100°C and the treatment time is 80min;
[0200] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0201] Example 5
[0202] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0203] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0204] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0205] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 5 parts of thermal insulation filler, 2 parts of black pigment, 2 parts of thermal sensitizer, 6 parts of cellulose;
[0206] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0207] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0208] Continue to add the thermosensitive agent and stir;
[0209] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0210] In the preparation method of the latex bead glue, the foaming amount is controlled at 40%, and the viscosity is controlled at 5500mPas.
[0211] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0212] 100 parts of natural latex, 2 parts of KOH, 1.2 parts of sulfur, 2 parts of zinc oxide, 0.9 parts of accelerator, 2 parts of antioxidant, 2 parts of black pigment, 3 parts of cellulose;
[0213] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0214] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0215] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0216] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 20% and the viscosity is controlled at 1200 mPas.
[0217] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0218] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0219] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0220] The compression molding process in step S2 includes the following steps:
[0221] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0222] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0223] Heating and maintaining the temperature at 105°C, pressurizing and maintaining at 0.3MPa;
[0224] After 1 minute, beads are formed on the surface of the glove core.
[0225] The height of the beads formed on the surface of the glove core is 6mm and the spacing is 2mm.
[0226] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0227] Wherein, the preheating treatment in step S3 includes the following steps:
[0228] The oven temperature was raised and maintained at 60°C;
[0229] The glove core was placed in an oven and baked for 15 min.
[0230] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0231] Wherein, the coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4%;
[0232] The homogenization time is 90s.
[0233] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0234] Pre-sulfur treatment is carried out after 60S of glue mixing;
[0235] The pre-sulfurization temperature is 80°C and the pre-sulfurization time is 40 minutes;
[0236] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0237] The temperature of the bath is 25℃ and the time of the bath is 20min.
[0238] The temperature of high temperature vulcanization treatment is 100°C and the treatment time is 80min;
[0239] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0240] Example 6
[0241] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0242] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0243] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0244] 100 parts of natural latex, 1 part of KOH, 0.8 parts of sulfur, 1.6 parts of zinc oxide, 0.6 parts of accelerator, 1 part of antioxidant, 3 parts of thermal insulation filler, 1 part of black pigment, 1 part of thermal sensitizer, 4 parts of cellulose;
[0245] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0246] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0247] Continue to add the thermosensitive agent and stir;
[0248] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0249] In the preparation method of the latex bead glue, the foaming amount is controlled at 20%, and the viscosity is controlled at 6500mPas.
[0250] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0251] 100 parts of natural latex, 1 part of KOH, 0.8 parts of sulfur, 1.6 parts of zinc oxide, 0.6 parts of accelerator, 1 part of antioxidant, 1 part of black pigment, 2 parts of cellulose;
[0252] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0253] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0254] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0255] In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 25% and the viscosity is controlled at 1000 mPas.
[0256] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0257] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0258] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0259] The compression molding process in step S2 includes the following steps:
[0260] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0261] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0262] Heat and maintain the temperature at 100°C, pressurize and maintain at 0.1MPa;
[0263] After 5 minutes, the beads are formed on the surface of the glove core.
[0264] The height of the beads formed on the surface of the glove core is 6mm and the spacing is 3mm.
[0265] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0266] Wherein, the preheating treatment in step S3 includes the following steps:
[0267] The oven temperature was raised and maintained at 55°C;
[0268] The glove core was placed in an oven and baked for 20 min.
[0269] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0270] Wherein, the coagulant in step S4 is a 3% by mass glacial acetic acid methanol solution;
[0271] The homogenization time is 80s.
[0272] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0273] Pre-sulfurization treatment is carried out after 120S of coating;
[0274] The pre-sulfurization temperature is 75°C and the pre-sulfurization time is 30 minutes;
[0275] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0276] The temperature for soaking and washing is 28℃ and the time for soaking and washing is 15min.
[0277] The temperature of high temperature vulcanization treatment is 95℃ and the treatment time is 60min;
[0278] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0279] Example 7
[0280] A method for preparing latex beaded heat-insulating gloves comprises the following steps:
[0281] S1. Prepare raw material glue: including latex bead glue and latex impregnation glue;
[0282] The raw materials used for the latex bead glue in step S1 are the following formula by weight:
[0283] 100 parts of natural latex, 3 parts of KOH, 1.6 parts of sulfur, 2.4 parts of zinc oxide, 1.2 parts of accelerator, 3 parts of antioxidant, 5 parts of thermal insulation filler, 3 parts of black pigment, 3 parts of thermal sensitizer, 8 parts of cellulose;
[0284] The above formula is prepared by the following configuration method to prepare the latex dot bead glue in step S1:
[0285] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0286] Continue to add the thermosensitive agent and stir;
[0287] Finally, cellulose is added to thicken the latex bead glue to obtain the finished product.
[0288] In the preparation method of the latex bead glue, the foaming amount is controlled at 35%, and the viscosity is controlled at 6500mPas.
[0289] The raw materials used for latex impregnation mortar in step S1 are the following formula by weight:
[0290] 100 parts of natural latex, 3 parts of KOH, 1.6 parts of sulfur, 2.4 parts of zinc oxide, 1.2 parts of accelerator, 3 parts of antioxidant, 3 parts of black pigment, 8 parts of cellulose;
[0291] The above formula is prepared by the following configuration method to obtain the latex impregnation slurry in step S1:
[0292] Add the formulated amount of KOH, sulfur, zinc oxide, accelerator, antioxidant and black pigment to the natural latex in sequence, mix and stir evenly, and foam;
[0293] Cellulose is added for thickening to obtain the finished latex impregnated mortar.
[0294] In the preparation method of latex impregnation slurry, the foaming amount is controlled at 30% and the viscosity is controlled at 1400mPas.
[0295] In the preparation of the above two types of mortars, diphenylthiourea is selected as the accelerator and antioxidant 2246 is selected as the antioxidant;
[0296] Glass micro beads are used as thermal insulation filler, and polysiloxane is used as thermal sensitizer.
[0297] S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process;
[0298] The compression molding process in step S2 includes the following steps:
[0299] Apply the latex dot glue paste on the gravure mold with the designed pattern;
[0300] Align the gravure mold with the area of the glove core to be dotted with beads, and then do bead planting;
[0301] Heat and maintain the temperature at 110°C, pressurize and maintain at 0.4MPa;
[0302] After 3 minutes, the beads are formed on the surface of the glove core.
[0303] The height of the beads formed on the surface of the glove core is 5mm and the spacing is 2.5mm.
[0304] S3, putting the glove core covered with beads in step S2 onto the hand model and performing preheating treatment;
[0305] Wherein, the preheating treatment in step S3 includes the following steps:
[0306] The oven temperature was raised and maintained at 58°C;
[0307] The glove core was placed in an oven and baked for 18 minutes.
[0308] S4, dipping the glove core preheated in step S3 into a coagulant for homogenization;
[0309] Wherein, the coagulant in step S4 is a 5% by mass glacial acetic acid methanol solution;
[0310] The homogenization time is 100s.
[0311] S5, taking the latex impregnation slurry in step S1, and then dipping the glove core treated in step S4 into the latex impregnation slurry to form a dipping layer on the surface of the glove core;
[0312] Pre-sulfurization treatment is carried out after 90S of coating;
[0313] The pre-sulfurization temperature is 90°C and the pre-sulfurization time is 35 minutes;
[0314] S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high temperature vulcanization treatment;
[0315] The temperature of the bath is 30℃ and the time of the bath is 18min.
[0316] The temperature of high temperature vulcanization treatment is 110℃ and the treatment time is 40min;
[0317] S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing 12 cm long and 5 cm wide heat-insulating cotton and flame-retardant glass fiber cloth to the base of the glove core rubber layer, with the heat-insulating cotton located between the rubber layer and the flame-retardant glass fiber cloth, to obtain a finished latex dot heat-insulating glove.
[0318] For the process steps of Examples 1 to 7, preferably, the high temperature vulcanization treatment in step S6 can be divided into two stages:
[0319] The first stage is heat drying at 95°C for 20 min;
[0320] The second stage is heat drying at a high temperature of 110°C for 60 minutes.
[0321] The performance indicators of the above different embodiments were tested through industry standard experiments, and the results are shown in the following table:
[0322]
[0323]
[0324] From the data in the table, we can see that latex beaded heat-insulating gloves have outstanding heat-insulating performance. After repeated experiments, the increase of bead height, the increase of bead bubble volume and the increase of bead filler ratio are all helpful to improve the heat-insulating performance, and have little effect on wear resistance. The designability of beads makes latex beaded heat-insulating gloves have good market applications.
[0325] It should be noted that this specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
Claims
1. A method for preparing latex beaded heat-insulating gloves, characterized in that: The following steps are involved: S1. Prepare raw material glue: including latex bead glue and latex impregnation glue; The raw materials used for latex impregnation mortar are the following formula by weight: 100 parts of natural latex, 1-3 parts of KOH, 0.8-1.6 parts of sulfur, 1.6-2.4 parts of zinc oxide, 0.6-1.2 parts of accelerator, 1-3 parts of antioxidant, 1-3 parts of black pigment, and 2-4 parts of cellulose; the above formula is used to prepare the latex impregnation mortar in step S1 by the following configuration method: KOH, sulfur, zinc oxide, accelerator, antioxidant, and black pigment in the formula amount are added to natural latex in sequence, mixed and stirred evenly, and foamed; cellulose is added for thickening to obtain the finished latex impregnation mortar; S2, taking the latex dot bead slurry in step S1, and forming the latex dot beads on the palm surface of the glove core by a compression molding process; S3, putting the glove core covered with beads in step S2 onto the hand model; raising the temperature of the oven and maintaining it at 55-60° C.; placing the glove core in the oven and baking it for 15-20 minutes for preheating treatment; S4, dipping the glove core preheated in step S3 into a coagulant for homogenization; S5, taking the latex impregnation slurry in step S1, and then immersing the glove core treated in step S4 into the latex impregnation slurry to form an impregnation layer on the surface of the glove core; performing pre-sulfurization after 60-120S of homogenization; the pre-sulfurization temperature is 75-90°C, and the pre-sulfurization time is 30-40min; S6, soaking and washing the glove core after the pre-sulfur treatment in step S5, and performing high-temperature vulcanization treatment; the soaking temperature is 25-30°C, and the soaking time is 15-20 minutes; the high-temperature vulcanization temperature is 95-110°C, and the treatment time is 40-80 minutes; S7, demoulding the glove core after high temperature vulcanization treatment in step S6, sewing a 12 cm long and 5 cm wide heat-insulating cotton and a flame-retardant glass fiber cloth to the base of the glove core dipped layer, with the heat-insulating cotton located between the dipped layer and the flame-retardant glass fiber cloth, to obtain a finished latex dotted heat-insulating glove; The raw materials used for the latex beading mortar in step S1 are the following formula by weight: 100 parts of natural latex, 1-3 parts of KOH, 0.8-1.6 parts of sulfur, 1.6-2.4 parts of zinc oxide, 0.6-1.2 parts of accelerator, 1-3 parts of antioxidant, 3-5 parts of heat-insulating filler, 1-3 parts of black pigment, 1-3 parts of heat-sensitive agent, and 4-8 parts of cellulose; the latex beading mortar in step S1 is prepared by the following configuration method: KOH, sulfur, zinc oxide, accelerator, antioxidant, heat-insulating filler, and black pigment in the formula amount are added to the natural latex in sequence, mixed and stirred evenly, and foamed; the heat-sensitive agent is continuously added and stirred; and finally cellulose is added for thickening to obtain the finished latex beading mortar; Apply the latex beading glue paste on the gravure mold with a designable pattern; align the gravure mold with the area of the glove core to be beaded, and implant the beads; heat and maintain the temperature at 100-110°C, and pressurize and maintain it at 0.1-0.4MPa; after 1-5 minutes, the beads are formed on the surface of the glove core; The height of the beads formed on the surface of the glove core is 4-6mm, and the spacing is 2-3mm.
2. The method for preparing the latex dotted heat-insulating gloves according to claim 1, characterized in that: In the preparation method of the latex bead glue, the foaming amount is controlled at 30±10%, and the viscosity is controlled at 6000±500mPas.
3. The method for preparing the latex dotted heat-insulating gloves according to claim 1, characterized in that: In the preparation method of the latex impregnation slurry, the foaming amount is controlled at 25±5%, and the viscosity is controlled at 1200±200 mPas.
4. The method for preparing the latex dotted heat-insulating gloves according to any one of claims 1 or 3, characterized in that: The accelerator is diphenylthiourea, the antioxidant is antioxidant 2246; the thermal insulation filler is glass beads, and the thermosensitive agent is polysiloxane.
5. The method for preparing the latex dotted heat-insulating gloves according to claim 1, characterized in that: The coagulant in step S4 is a glacial acetic acid methanol solution with a mass fraction of 4±1%; the homogenization time is 80-100s.
Citation Information
Patent Citations
Aerogel modified latex, heat insulation gloves and preparation method
CN112878062A
Thermal -insulated some pearl gloves
CN207054910U